Economic reforms in the Euro area: Is there a common agenda? - Xavier Debrun; Jean Pisani-Ferry (Bruegel, 2006)
Visiting scholar Xavier Debrun, and Bruegel director Jean Pisani-Ferry contribute to the emerging discussion on reform strategies in the euro area. An earlier version of this note was presented to the Eurogroup Working Group of the Economic Policy Committee of the EU.
Keywords: 330; Wirtschaftspolitik; Wirkungsanalyse; Europäische Wirtschafts- und Währungsunion; EU-Staaten